Implementasi Manajemen Berbasis Sekolah Dalam Meningkatkan Kualitas Sekolah SDS Al-Hikmah Indonesia - Nursaadah, Nursaadah; Umar, Abu Bakar; Waluyo, Kasja Eki (Jurnal Ilmiah Wahana Pendidikan, 2025)
School based management is an alternative in the management of education that emphasizes the independence and creativity of schools in order to improve the quality of education. School Based Management is carried out in order to provide convenience in achieving the vision, mission and goals of the institution, so as to improve the quality of education and provide good and quality final results, as well as to obtain productive education and quality graduates. The purpose of this study was to analyze: Implementation of School Based Management, Role of the Principal in Implementing School Based Management, Obstacles in Implementing School Based Management, Effects of School Based Management on Student Achievement, Key Factors for the Success of School Based Management. This research method is qualitative with a case study design, data collection techniques through observation, documentation and interviews. The data source is the Principal of SDS Al-Hikmah, Cikampek. The results of the study show that: 1. The implementation of MBS SDS Al-hikmah has been carried out through teacher competency education and training, improving infrastructure, improving the quality of education management, to school and community relations, 2. There are seven roles of school principals in implementing School Based Management, 3. Obstacles that occur are the placement of tasks and authorities that are not appropriate, the assignment of school employee performance that is not satisfactory, 4. The influence of MBS on student achievement makes the learning process more creative, optimistic, and confident, 5. The success factor of MBS is The Right man on the right place which means occupying the tendon in the right position